(3OjhGf GdNHR CQRjs - (3CHhGdbGSe fUQ Hf CMeO GdNHR GQRj,J (B317 (3g` s ((3CMeO Hf GdMSjf Hf ESeGYjd Hf YHOGddg GdEeGe s)
(3ChdgG (B:s
(3fSje YHjQ aj YdGdI eGA hJeKGd fhQ aj COje ghGA s
(3BNQgG (B:s
(3hBNQg(B: (3aj bGajI GdgGA adh JQi MSfI ef Hjf MSfge dbdJ PG edc CMaJ Hg GdhRQGA s
(3Vef eLehY , JQJjHgG (B: (3ef U (B41 - (3U(B123s
(3GdOjhGf eQJH Ydi GdbhGajs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B88s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B94 s
Keywords: (3GdCOHs